2013
DOI: 10.1371/journal.pone.0067921
|View full text |Cite
|
Sign up to set email alerts
|

Hedysari Extract Improves Regeneration after Peripheral Nerve Injury by Enhancing the Amplification Effect

Abstract: Radix Hedysari is an herbal preparation frequently used in traditional Chinese medicine. It can promote regeneration after peripheral nerve injury, but its effect on the amplification ratio (the ratio of distal to proximal fibers) during peripheral nerve regeneration has not yet been examined. In this study, we explored the effect of Hedysari extract on the amplification ratio in the peripheral nerve. Male Sprague-Dawley rats were separated into three groups at random: normal group (without surgery), model gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Many studies have shown that various types of vitamins such as vitamin B complex, vitamin B12 (Altun & Kurutas, ), vitamin E (Elsy, Khan, & Maheshwari, ), vitamin D3 (Chabas et al, ), vitamin D2 (Chabas et al, ), and vitamin C (Gess, Rohr, & Young, ) are effective in nerve regeneration. In addition, joint application of Radix Hedysari plant extract, an herbal preparation often used in traditional Chinese medicine, combined with a chitin conduit could efficiently promote the growth of lateral buds in the proximal nerve stump and considerably improve regeneration in a peripheral nerve injury model (Wang et al, ). Liu et al () have also demonstrated that Salidroside, a derivative of Rhodiola rosea L. plant, can promote nerve regeneration in cellular nerve scaffolds through salidroside‐induced neurotrophin secretion in SCs.…”
Section: Other Factors For Nerve Regenerationmentioning
confidence: 99%
“…Many studies have shown that various types of vitamins such as vitamin B complex, vitamin B12 (Altun & Kurutas, ), vitamin E (Elsy, Khan, & Maheshwari, ), vitamin D3 (Chabas et al, ), vitamin D2 (Chabas et al, ), and vitamin C (Gess, Rohr, & Young, ) are effective in nerve regeneration. In addition, joint application of Radix Hedysari plant extract, an herbal preparation often used in traditional Chinese medicine, combined with a chitin conduit could efficiently promote the growth of lateral buds in the proximal nerve stump and considerably improve regeneration in a peripheral nerve injury model (Wang et al, ). Liu et al () have also demonstrated that Salidroside, a derivative of Rhodiola rosea L. plant, can promote nerve regeneration in cellular nerve scaffolds through salidroside‐induced neurotrophin secretion in SCs.…”
Section: Other Factors For Nerve Regenerationmentioning
confidence: 99%
“…Despite the development of several surgical techniques15, new bridging materials16171819, and therapies2021222324, the autologous nerve graft is still the “gold standard” in long peripheral nerve gap reconstruction. Although there are some disadvantages to the procedure, such as a lack of autologous nerve sources or feeling obstacles for providing area during surgery, the autologous nerve graft is closest to the normal physiological structure and function when the above-noted difficulties can be overcome.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have manifested that actin cytoskeleton reorganization is a crucial factor in many cellular progress, including cell proliferation (Charvet et al 2006;Papakonstanti and Stournaras 2008;Yue et al 2011), migration, and differentiation (Konakahara et al 2011. It is reported that lots of traditional Chinese medicine can ameliorate SNC (Zou et al 2013) and promote peripheral nerve regeneration (Kou et al 2013;Wang et al 2013b). These all forced us to question whether Re participating in the cytoskeleton reorganization may play a vital role in regulating the proliferation and differentiation of SCs after SNC.…”
Section: Discussionmentioning
confidence: 99%